2010
DOI: 10.1111/j.1365-2796.2010.02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and frailty in older Americans

Abstract: Objective. To explore the relation between 25-hydroxyvitamin D deficiency and frailty. Frailty is a multidimensional phenotype that describes declining physical function and a vulnerability to adverse outcomes in the setting of physical stress such as illness or hospitalization. Low serum concentrations of 25-hydroxyvitamin D are known to be associated with multiple chronic diseases such as cardiovascular disease and diabetes, in addition to all cause mortality.Design. Using data from the Third National Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 34 publications
9
70
0
3
Order By: Relevance
“…Taken together, these findings indicate that the association between low 25OHD values and orthostatic hypotension is more likely to relate to the fact that individuals with a poor vitamin D status also had more of the factors known to be associated with orthostatic hypotension. 30,31 Our findings are consistent with a recent work by McCarroll et al 11 demonstrating that 25OHD levels were significantly lower in patients with orthostatic hypotension, but they were not associated with impaired orthostatic hemodynamic parameters. The literature on the possible relationship between 25OHD and orthostatic hypotension in younger people is of limited value.…”
Section: Discussionsupporting
confidence: 83%
“…Taken together, these findings indicate that the association between low 25OHD values and orthostatic hypotension is more likely to relate to the fact that individuals with a poor vitamin D status also had more of the factors known to be associated with orthostatic hypotension. 30,31 Our findings are consistent with a recent work by McCarroll et al 11 demonstrating that 25OHD levels were significantly lower in patients with orthostatic hypotension, but they were not associated with impaired orthostatic hemodynamic parameters. The literature on the possible relationship between 25OHD and orthostatic hypotension in younger people is of limited value.…”
Section: Discussionsupporting
confidence: 83%
“…37 Bone health closely mirrored overall health: Frailty characterized over one out of four subjects in the lowest BMD cluster, but less than 1% of those in the highest BMD cluster. Frailty is an important marker of the risk of impending or worsening disability, hospitalization, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting a role for vitamin D includes the fact that polymorphisms in vitamin D have been linked to muscle strength (39); also frailty (a condition which has some overlap with sarcopenia) has been shown to be associated with vitamin D deficiency (40). As with protein supplementation, intervention trials of the effect of vitamin D on strength and physical performance have shown mixed results, however (41).…”
Section: Dietmentioning
confidence: 99%